AN INTERPRETATIVE PHENOMENOLOGICAL ANALYSIS OF RELIGIOUS ORIENTATION IN EMERGING ADULTS AND ELDER PEOPLE OF PAKISTAN - Moazama Anwar, Najma Iqbal Malik (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The present hermeneutic phenomenological study explored the subjective experience of religious orientation in emerging adults and elder people of Pakistan. Purposive sampling technique and the semi-structured interviewing procedure was utilized to record the lived experiences of 7 individual (4 male and 3 female). Phenomenological Analysis was utilized to analyze the transcripts (Smith, 2004) and quality checks were implemented to increase the validity of the analysis. Three main themes were identified. Intrinsic religious orientation with subthemes of code of life, religious faith and doctrine, religious denigration and prayers. Extrinsic religious orientation with subthemes of extrinsic-personal and extrinsic-social. Quest religious orientation with a subtheme of religious authenticity,religious doubts, religious angst, tentativeness and flexibility, religious belief modification, knowledge enhancement and existential Motives. The implications of the study are discussed concerning raising awareness about the importance of religious orientation in one’s life. Limitations and suggestions of study for future endeavours have also been discussed.